Integrasi Agama dan Sains Perspektif Teori Quantum Nidhal Guessoum - Rozikin, Ahmad Zainor; Amalih, Ihwan (Medan Resource Center, 2023)
The debate between religion and science remains a captivating subject of study. The conflict intensifies as scientists, viewing themselves as rational, aim to uncover fundamental laws governing behavior, matter, and style. Conversely, religionists adhere to unchangeable truths based on religious dogmas. Interestingly, Muslim scientist Nidhal Guessoum addresses modern science from a different perspective, integrating religion and science, thus enriching Islamic thought. This study examines the construction and relationship between religion and science in Guessoum's quantum theory. Using qualitative research methods, it analyzes books and research journals detailing Guessoum's thoughts. The findings reveal that Guessoum constructs an Islamic view on scientific theories, including Islam and Cosmology, Design Arguments, Anthropic Principles, and Evolution. Additionally, he offers a quantum theory based on three principles: non-contradiction, layered interpretation, and theistic falsification.